"We're number fat!": reflections on fat fastpitch with the heavy hitters. Issue 3 (2nd September 2021) - Oliver, Diandra; Cameron, Layla
ABSTRACT: This paper tells the story about the formation of the Heavy Hitters, a fat-identified softball team in Vancouver, British Columbia. The Heavy Hitters responded to chronic fatphobia in the city by building fat community through organized sports. Since physical activity is categorized as "something only 'the athletes' do", fat people often negotiate fatphobic discourses when participating in group sports. These discourses negatively prescribe fat subjectivity while also emphasizing feelings of "alienation, dread, and disembodiment". Further, in group sports, many fat people carry lifelong memories and feelings of humiliation, vulnerability and incompetency resulting from multi-layered experiences of fat stigma and exclusion. Utilizing collaborative autoethnography, the authors synthesize their experiences forming and playing on the Heavies within relevant literature and theories of fat activism (e.g. Ellison et al., 2016). This paper brings together the authors' previous interdisciplinary approaches to issues of fatphobia and gatekeeping in organized and individual sports in efforts to challenge academic conventions which continue to center medicalized and healthist understandings of the "whys" fat people move their bodies. By focusing on the Heavies' shared and intentional activisms against fat stigma, this paper offers new ways to imagine a future where fat athletes inject activism into physical activity by rejecting weight-loss culture and enjoying sports in the bodies that they have right now.